2014
DOI: 10.1007/s00787-014-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of schizophrenia spectrum disorders in early-onset first episodes of psychosis: a support vector machine model

Abstract: Identifying early-onset schizophrenia spectrum disorders (SSD) at a very early stage remains challenging. To assess the diagnostic predictive value of multiple types of data at the emergence of early-onset first-episode psychosis (FEP), various support vector machine (SVM) classifiers were developed. The data were from a 2-year, prospective, longitudinal study of 81 patients (age 9-17 years) with early-onset FEP and a stable diagnosis during follow-up and 42 age- and sex-matched healthy controls (HC). The inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 52 publications
1
24
0
1
Order By: Relevance
“…We extracted the mean FA, MD, ODI, and ND for control subjects and patients with FEP in the corpus callosum body (Johns Hopkins University ICBM-DTI-81 atlas), masking the region of interest by the mean_FA_skeleton_mask to include only skeleton voxels (Supplemental Figure S2). Years of Education 13.37 (11)(12)(13)(14)(15)(16)(17) 13.84 (11)(12)(13)(14)(15)(16)(17) .…”
Section: Region Of Interest Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…We extracted the mean FA, MD, ODI, and ND for control subjects and patients with FEP in the corpus callosum body (Johns Hopkins University ICBM-DTI-81 atlas), masking the region of interest by the mean_FA_skeleton_mask to include only skeleton voxels (Supplemental Figure S2). Years of Education 13.37 (11)(12)(13)(14)(15)(16)(17) 13.84 (11)(12)(13)(14)(15)(16)(17) .…”
Section: Region Of Interest Comparisonmentioning
confidence: 99%
“…These structural changes are associated with dysfunctional interactions between brain regions (12) and predict symptom severity in FEP (13). Moreover, neuroimaging indices of white matter integrity predict longer term outcomes, including response to treatment (2,14). White matter structural abnormalities may thus underpin early psychosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results demonstrated that there was an accuracy rate of 88.3% for classification in the first group, and the discrimination function derived from the first group correctly differentiated 75% of the subjects in the second group. To integrate spatial and temporal information in multichannel fNIRS, [8] employed a novel probabilistic pattern recognition method called Gaussian process classifier for the diagnostic classification of schizophrenia. Using the temporal patterns of fNIRS data measured during a working memory task, an overall accuracy of 76% was achieved in a group of 80 samples.…”
Section: Introductionmentioning
confidence: 99%
“…One study used a K-nearest neighbors (KNN) algorithm, random forest model, and a support vector machine (SVM) with a linear kernel function and radial basis function (RBF) to classify the different levels of airway obstruction in patients with chronic pulmonary diseases in a binary fashion [ 8 ]. A binary SVM classifier was used for the identification of schizophrenia spectrum disorders (SSD) in the early stages and the assessment of the predictive value of early diagnosis of different types of data in the emergence of first episode psychosis (FEP) [ 9 ]. Another study has been conducted on the methods of diagnosis of lymphglands based on SVM with different kernel functions such as linear, quadratic, and Gaussian functions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%